The Use of Emotion Response Method for Consumer AcceptanceTesttoFisheries Product - Tian Nur Ma’rifat (Universitas Darussalam Gontor, 2020)
In development of sensory test methods on food products, several methods have been used to measure the level of consumer acceptance, one of which isemotionresponse method. This study discusses the use of emotion response method for consumer acceptance of food products in the past 10 years and analyzes the use of thismethod to increase consumer acceptance of fishery products specifically. The methodused in this research is literature review using content analysis. From the review of publications published in the reputable journal, the emotion response method has been used for the past 10 years for consumer acceptance of the characteristics of food products, with a limited number of articles. Fishery products are possible tobe measuredusing emotion response method with previously sensory attributes must be mapped according to the products specific atributes, such as umami, fishy or fish aroma